(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
The development and location of agricultural land reclamation is directly related to climatic changes. Today, the problem of adaptation of agricultural production, as the most sensitive and vulnerable to climatic factors, comes to the forefront.